PENINGKATAN HASIL BELAJAR SISWA KELAS IV PADA PELAJARAN IPAS MATERI MENGUBAH BENTUK ENERGI MELALUI PENERAPAN MODEL PBL DI SD INPRES LASIA - Elisa Pinto, Jannes Bastian Selly; Netty E. A. Nawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to improve student learning outcomes by applying the PBL model to the topic of Energy Transformation for 4th-grade students at SD Inpres Lasiana. The study involved 27 students (15 males and 12 females) and used observation, tests, and documentation for data collection. Data analysis was conducted descriptively, both qualitatively and quantitatively.The results showed that in Cycle I, 18 students (67%) achieved mastery due to active participation, good understanding of the material, effective group work, and test-solving skills. Meanwhile, 9 students (33%) did not achieve mastery due to lack of concentration and difficulty with test questions. In Cycle II, student learning outcomes improved, with 23 students (85%) achieving mastery due to increased engagement and better test performance. The remaining 4 students (15%) will receive remedial support.The study concludes that the PBL model effectively enhances student learning outcomes on Energy Transformation for 4th-grade students at SD Inpres Lasiana.